Study on bagging effect and rupture failure of membrane structures. (1st April 2021) - Samy, Akram; Yuan, Xingfei; Zhang, Ying; Zhang, Weijia
Highlights: Bagging effect of membrane structures under heavy rain is studied with VFIFE method. Numerical results of Rupture propagation are compared with balloon tests. Inflatable fabrics are easily affected by partial loads and depress fast. Tension fabrics form larger depression under persistent rain and rapture fast. Heavy precipitation causes much more irreparable devastation to inflatable films. Abstract: Bagging effect refers to the expansion of local depression on the film surface when the membrane structures are subject to persistent rainfall. In previous engineering cases, bagging effect caused dramatic destruction of large-span roofs under the extreme weather events. In this work, we investigated the rupture mechanism of membrane structures induced by bagging effect, and simulated the whole process by means of the vector form of intrinsic finite element (VFIFE) method. The vectorized analog equation of particle motion was derived from the second type of Lagrange equation. Several efficient approaches were proposed subsequently to simulate the cumulative precipitation and fracture mode. The numerical examples presented the overall procedure from the initial shape to the rupture propagation of two types of membranes. The results show that inflatable fabrics depress fast under the same initial imperfection factors, while tension fabrics rupture fast under the same rainfall intensity. The proposed method in this study provides practical references for the bagging analysis of membrane structures.